Analysis of BPM and Temperature Data Retrieval in Smartband Design with Android Applications Using the Multiplexing Method - Jarot Hadi Wibowo; Her Gumiwang Ariswati; I Dewa Gede Hari Wisana; Shubhrojit Misra (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2023)
Monitoring and recording of patient medical records is very necessary if there are symptoms of a disease that must be taken quickly so that the patient's condition does not worsen and find out how the pattern of a disease attacks the body's condition, this is so that the patient's history data can be checked by a doctor to make it easier and improve the accuracy of the doctor's diagnosis. In its application, the use of two sensors for smartband requires the use of a multiplexer method so that the data does not collide with each other because of the similarity of the two sensor systems. In this study, the Wemos D1 Mini microcontroller was used to process BPM and temperature data, as well as to process the time of using the multiplexer of the two sensors, then the BPM and temperature values ​​were displayed on the OLED screen. Based on the results of the research that has been done, it can be concluded that the smartband has an error (error value) which is still within the allowable tolerance limit of ±5%. This study has the advantage of a portable device design and is very suitable for daily use to monitor the patient's condition, so that patients are not disturbed by the presence of this smartband. This research has a development that is the use of a larger battery so that its use can last longer, then the use of a temperature sensor that has a medical grade standard.